1982
DOI: 10.1007/bf00690581
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-related RNA sequences in human neurogenic tumors

Abstract: Thirty two human tumours, mainly neurogenic, have been investigated for the presence of adenovirus-related RNA sequences. 3H-labelled tumour virus DNA probes derived from human adenoviruses types 2 and 12, bovine adenovirus type 3, and avian adenovirus CELO were hybridized in-situ on tumour kryostat sections under conditions that detect complementary RNA. Tumour virus-related RNA was detected in 62% of all tumours tested, but was not detectable in normal human brain tissues. Expression of tumour virus-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The most extensive and careful of these studies, by Green and colleagues (54–58) and Mak et al (59), were uniformly negative. Although detection of Ad‐related RNA sequences in human neurogenic tumors by in situ hybridization has been reported (60), this finding has not been confirmed using more sensitive and reliable technologies. Ads are relatively lytic, normally killing cells in which they replicate, thus rendering them unlikely to form tumors in their natural host and explaining why transformation of human cells by human Ads requires sheared or cloned viral DNA rather than intact DNA or virus.…”
Section: Discussionmentioning
confidence: 94%
“…The most extensive and careful of these studies, by Green and colleagues (54–58) and Mak et al (59), were uniformly negative. Although detection of Ad‐related RNA sequences in human neurogenic tumors by in situ hybridization has been reported (60), this finding has not been confirmed using more sensitive and reliable technologies. Ads are relatively lytic, normally killing cells in which they replicate, thus rendering them unlikely to form tumors in their natural host and explaining why transformation of human cells by human Ads requires sheared or cloned viral DNA rather than intact DNA or virus.…”
Section: Discussionmentioning
confidence: 94%
“…The finding that normal host cells contain endogenous seqences with a high degree of homology to potential tumour virus RNA and DNA introduces a note of caution into the interpretation of hybridisation data obtained when either the probe or target is of high complexity. For example, the in situ hybridisation experiments of Maitland et al (1981) and Ibelgaufts et al (1982) which indicated that cells from some cervical or neurogenic tumours contained Ad2-related RNA sequences, were performed under conditions corresponding to -Tm -25°C. We show here that, under such conditions, virus-negative cell RNA hybridises efficiently to Ad2 DNA ( Figure 8).…”
Section: Dna-dna Hybridisation Experimentsmentioning
confidence: 99%
“…It is generally recognised that EBV is associated with, and probably is a contributing factor to the development of two human malignancies, African Burkitt's lymphoma and poorly differentiated nasopharyngeal carcinoma (Epstein, 1978). On the contrary, extensive studies (Green and Mackey, 1977;Green et al, 1979;Mackey et al, 1976Mackey et al, , 1979Wold et al, 1979) have failed to show an association between adenoviruses and any type of human cancer with the tentative exception of some neurogenic tumours (Ibelgaufts et al, 1982). However, lymphoid neoplasms, in particular leukaemias, have not been well represented in previous investigations of adenovirus-associated tumour diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Antigens, DNA, and RNA from both DNA and RNA viruses have been found in human meningiomas. 65,67,155,156 Interest has particularly centered on the papovavirus large T antigen, which has been identified in a significant number of meningiomas by immunohistochemistry. 157 Also, papovavirus DNA sequences have been identified in meningiomas.…”
Section: The Role Of Oncogenic Viruses In Meningioma Etiology Is Unclearmentioning
confidence: 99%